Is the Chemotherapy Era in Advanced Non-Small Cell Lung Cancer Really Over? Maybe not Yet. Issue 3 (May 2016) - Lo Russo, Giuseppe; Imbimbo, Martina; Garassino, Marina Chiara
Lung cancer is one of the most frequently diagnosed tumors in both the male and female population. In Italy it is the leading cause of cancer deaths in men and the third in women. Although the 5-year survival rate has moderately increased in the last years, the diagnosis remains associated with a very poor prognosis. However, in the last decade significant progress has been made, also in the treatment of advanced-stage non-small cell lung cancer. The advent of targeted therapies and the recent explosion of immunotherapy seem to have limited the role of chemotherapy. But is this completely true? The aim of this editorial is to discuss some of the most controversial aspects of the therapeutic scenario in non-small cell lung cancer, with particular attention to the role that chemotherapy still plays.